A disposable glass-based immunosensor for monitoring the cancer biomarker CEA in urine - Truta, Liliana A.A.N.A. (2015)
NanoPT 2014 International Conference, in Portugal, on February 12-14. Poster presentation based on topic Nanobio/Nanomedicine